Temple 8 in the Baroli group of temples dedicated to Ganesha - Temples of India Project Team (Jio Institute, 2024)
Temple 8 in the Baroli group of temples is a small temple dedicated to Ganesha and faces south. The temple has a garbhagriha (sanctum sanctorum) and a small kapili. The shikhara (superstructure) of the temple has collapsed.